2016
DOI: 10.1016/j.ekir.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulopathy Associated With Moderate Obesity

Abstract: IntroductionObesity-related glomerulopathy is an established secondary glomerular disease that may occur in obese individuals with a body mass index (BMI) of ≥30 kg/m2. However, patients with moderate obesity (BMI ≤ 30 kg/m2) may also develop this disease.MethodsA total of 20 patients with grade 1 obesity (25 ≤ BMI < 30 kg/m2) with persistent proteinuria, without evidence of other renal diseases, were analyzed retrospectively. These patients were compared with 20 patients with grade 2 or higher obesity (BMI ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…An expert renal pathologist made the diagnoses according to the international histological classification [ 18 ]. The area of tubulointerstitial damage was semi-quantitatively evaluated in renal cortical tissue [ 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…An expert renal pathologist made the diagnoses according to the international histological classification [ 18 ]. The area of tubulointerstitial damage was semi-quantitatively evaluated in renal cortical tissue [ 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that, among patients with even a moderate degree of obesity (BMI values < 30 kg/m 2 ), a subgroup exists that demonstrates the clinical and histopathological characteristics of typical ORG. 8 , 63 …”
Section: Renal Alterations In Obesity or Obesity-related Renal Impairmentioning
confidence: 99%
“…We further examined possible additional lesions consistent with obesity-related glomerulopathy (ORG). e glomerular density (the number of nonsclerotic glomeruli per renal cortical area) measured using an image analysis program (Aperio ImageScope, Leica, Bu alo Grove, IL, USA) was 1.7 mm 2 , which was low compared with that in nonobese kidney donors and comparable to the reported glomerular density in patients with ORG [9]. GBM width of the nonsclerotic area of the glomerulus with perihilar sclerosis was expected to be thick or normal in ORG [10], however, electron microscopic specimen including the glomerulus was not obtained.…”
Section: Case Reportmentioning
confidence: 55%